Numerical Simulation on the Influence of Injection Location, Injection Angle, and Divergence Half Angle on SITVC Nozzle Flow Field - H. R. Noaman; Hai Bin Tang; Elsayed Khalil (International Journal of Aerospace Engineering)
A numerical study has been performed to characterize the nozzle flow field of secondary injection thrust vector control (SITVC) and to estimate the performance parameters of SITVC. After validating the CFD turbulence models with an experimental data, a numerical simulation has been conducted in order to investigate the influence of changing the injection location, the injection angle, and the primary nozzle divergence half angle on the SITVC nozzle flow field structure and on the SITVC performance parameters. The secondary mass flow rate was kept constant for all cases during the simulation. The results showed that downstream injection near the nozzle exit Mp=2.75 increases the high-pressure zone upstream the injection leading to an increase in the side force; also, the higher divergence half angle 15° slightly increases the side force and it provides a wide range of deflection without shock impingement on the opposite wall becoming more effective for SITVC. The injection angle in the upstream direction 135° increases the side force, and by decreasing the injection angle to downstream direction 45°, the side force decreases. However, the SITVC performance parameters and the flow field structure are more influenced by the injection location and the primary nozzle divergence half angle while being less influenced by the injection angle.